Increased risk of death with codeine use in the elderly over 85 years old and patients with respiratory disease: A case-control study using retrospective insurance claims database. Issue 38 (18th September 2020) - Tchoe, Ha jin; Jeong, Sohyun; Won, Dae Yeon; Nam, Jin Hyun; Joung, Kyung-In; Shin, Ju-Young
Abstract : Abstract: To investigate the risk of mortality associated with exposure to codeine, considering various risk groups, using population-based national insurance claims data. National sample cohort data from the National Health Insurance Service of South Korea (2002–2013) was used in this case-control study. Cases were defined as patients with a death record between January 1, 2002 and December 31, 2013. Each case was matched to 10 controls based on age, sex, baseline comorbidities, and year of death. Definition of exposure was codeine prescription in 30 days prior to death and sensitivity analyses were performed for 15 and 60-day exposures. Adjusted odds ratios (aORs) with 95% confidence intervals (CIs) were estimated using conditional logistic regression adjusting for benzodiazepine, other opioids, anesthetics, hypnotics, CYP2D6 inducer, CYP3A4 inducer, and the Charlson comorbidity index. A total of 19, 341 cases and 185, 700 matched controls were included. The overall risk associated with codeine use and mortality risk was not significant (aOR 1.08, 95% CI 1.00–1.16). Sensitivity analyses with different exposure time window also presented similar insignificant results. However, in the subgroup analyses, codeine use was associated with an increased risk of mortality in the >85-year-old age group (aOR 2.38, 95% CI 1.26–4.48) and patients with respiratory disease (aOR 1.29, 95% CI 1.17–1.42). Although no statistically significant association was found in codeine exposure and mortality risk between cases and controls, we demonstrated that the elderly over 85 years old and patients with respiratory disease are associated with a higher risk with codeine exposure. Therefore, a more cautious practice of codeine prescription in these groups might be needed. Abstract : Supplemental Digital Content is available in the text